Meningkatkan Kualitas Pembelajaran Melalui Penerapan Strategi Pembelajaran Kooperatif - Delita Marni; Liza Amelia; Gusmaneli Gusmaneli (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This abstract discusses cooperative learning strategies and their benefits in improving the quality of learning. Cooperative learning is a learning strategy in which students learn in small, heterogeneous groups to achieve common goals. This strategy has several goals, namely improving academic achievement, acceptance of diversity, and development of social skills. Cooperative learning strategies are effective learning strategies to improve the quality of learning. Factors that influence the success of cooperative learning strategies must be considered and implementation steps must be taken appropriately.